Multi-Station Short Baseline Lightning Monitoring System - Wan Ismail, Ibrahim; Amir, A.S.M (2012)
Lightning is a natural phenomenon where the charges generate due to cloud, air movement or other turbulence atmospheric condition. The lightning can occur between cloud to cloud, cloud to air and cloud to ground. The lightning strike gives a big impact in our daily life such as it will kill people and animal,interruption on transmission line; destroy the building and other electrical equipment. These problems can be managed by using Lightning Detection System and the location method to detect and locate the lightning strike. This paper introduced the multi-station short baseline of VHF using Time-of-Arrival (TOA) method. A NI-DAQ 6212 was used to connect the antennas to the personal computer for display and data storage by using LabVIEW. The azimuth and elevation angle was calculated to determine the location of lightning stroke.